(3cJGH MOGFb GdCfhGQ aj YdGL GdCHUGQs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3CMSf eG aJM Hg GdfGWb aeg MeO GdChd HdG GHJOGA hGdBNQ HdG GfJgGA hHYO aEfg LQi ai ebQ GdMb hebYO GdUOb PcQ UfGYI GdYjf heG jdMbgG ef GdCeQGV s
(3BNQgG (B:s
(3hjVeO CjVkG HeM HjVI hOgJ hQO ZeSJ ajg bWfI hjcKQ UGMHgG GdCVWLGY Ydi baGg hGdgd GdTGai Je GdJCdja s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B633s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs